Youth Driven Engagement in the Homestay Program - Hairuddin Bin Harun; Abdul Rasid Bin Abdul Razzaq; Norzella Binti Bokhari (Faculty of Engineering, Universitas Negeri Yogyakarta, 2017)
Community-based tourism (CBT) is one of the tourist attracting ways involving local community which aims to develop and to enhance the era as well as to bring renewal to the local community. It includes the involvement of youth. CBT comes in various types and this study was conducted to find how CBT can create youth engagement in the homestay program. There were various factors that motivate youth to participate in homestay program. This study involved one case study of a qualitative study conducted in a district in Sabah, namely in Kundasang. In this study, Mersilou Homestay and Walai Tokou Homestay were chosen to be used as a place of study to review factors youth engagement in the homestay program. Data collection was through interviews in partial structures. Data were analyzed using NviVo 10 software and based on certain themes. The findings shown that there were several factors which drive engagement of youth in the homestay program in terms of interests, income, parental encouragement and comfort working in their own areas. In conclusion, the engagement of youth in the homestay program is based on the factors discovered in the study.